Extreme Hot Weather Has Stronger Impacts on Avian Reproduction in Forests Than in Cities - Pipoly, Ivett; Preiszner, Bálint; Sándor, Krisztina; Sinkovics, Csenge; Seress, Gábor; Vincze, Ernő; Bókony, Veronika; Liker, András (Frontiers in Ecology and Evolution, 2022)
Climate change and urbanisation are among the most salient human-induced changes affecting Earth's biota. Extreme weather events can have high biological impacts and are becoming more frequent recently. In cities, the urban heat island can amplify the intensity and frequency of hot weather events. However, the joint effects of heat events and urban microclimate on wildlife are unclear, as urban populations may either suffer more from increased heat stress or may adapt to tolerate warmer temperatures. Here we test whether the effects of hot weather on reproductive success of great tits (Parus major) are exacerbated or dampened in urban environments compared to forest habitats. By studying 760 broods from two urban and two forest populations over six years, we show that 14-16 days-old nestlings have smaller body mass and tarsus length, and suffer increased mortality when they experience a higher number of hot days during the nestling period. The negative effects of hot weather on body mass and survival are significantly stronger in forests than in urban areas, where these effects are dampened or even reversed. These results suggest that urban birds are less vulnerable to extreme hot weather conditions than their non-urban conspecifics, possibly by adaptively evolving or flexibly adjusting nestling physiology to tolerate heat stress, and/or by adjusting parental behavior in response to heat. This finding highlights that some endothermic vertebrates may be able to adapt to heat stress, which may help their populations cope with the joint challenges of climate change and urbanisation.